SUKUK WAQF FOR THE DEVELOPMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS - Syamsuri Syamsuri; Eka Risana Putri; Anisa Rosdiana Zein; Resi Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2021)
Education becomes an urgency in improving the quality of human life. Improving the quality of education is one of the goals of maqashid shariah, waqf as the property of the people whose benefits are intended for the continuity of the benefit of the people becomes one of the potential to be associated as a source of provision of educational institutions to improve the quality of human resources, considering that man is the caliph fil ardl and as an agent of change. The purpose of this study will explain about sukuk waqf in the development of Islamic education. In this study, the authors used qualitative research types using descriptive analysis. Information and data obtained from various sources from related aspects related to research issues with the source of books, journals, or other sources relevant to the discussion with the aim to reach conclusions about the benefit of sukuk waqf in the development of Islamic educational institutions. Waqf and sukuk integrated will be two phenomenal financial instruments by combining modern schemes of waqf asset development with securities that produce sukuk waqf. In integrating sukuk wakaf, educational institutions can use innovative product waqf models by using sukuk issued by waqf institutions as nadzir, as well as istitusi as third parties. This paper is limited by the scope of discussions related to waqf and Islamic educational institutions, as well as sukuk waqf that can be used as one of the innovations in the development of waqf assets in educational institutions. This research is expected to be used by practitioners of waqf, wakif, nazir, to be used as material in the management and development of productive waqf, especially in Islamic educational institutions.